VISUAL SEXUAL STIMULATION THROUGH THE AMYGDALA MAY AFFECT THE INDIVIDUALS EMOTIONAL STATE - Akhtari, Zeinab; Salehi, Maryam; Saghian, Mohammad; Sahraie, Hedayat; Norouzi, Saba (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The nature of sexual stimulation in the brain is not well established. In this regard, the role of emotional brain (which is called as the amygdaloid complex) needs to be evaluated more precisely. The amygdala is a silent region in the temporal part of the brain which has enriched connections with the parts of the brain both involved in the cognition functions and sensory information process. These connections gives the amygdala to receive unique information from visual cortex about the environments as well as other parts of the body, merge these information and produce sufficient outputs to the different parts of the frontal cortex to exhibit a behavior relevant to the stimulation. The present study tries to review the data exist about this function of the amygdala.